Comparison of Maternal Outcomes between Clinical and Subclinical Hypothyroid Pregnant Women admitted in a Subspecialty Department of a Tertiary Hospital (Journal of Current and Advance Medical Research, 2021)
Background: Women with Hypothyroidism have higher pregnancy complication rates.Objective: The purpose of the present study was to compare the effects of clinical and subclinical hypothyroidism on maternal outcomes.Methodology: This cohort study was conducted in the Feto-Maternal Department of  Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh from a period of 6 months dated from September 2019 to February 2020 for a period of 6 months. All cases of the clinical and sub-clinical hypothyroid pregnant women admitted in this department. Maternal outcomes of both groups during pregnancy were recorded. Findings of the cases recorded carefully.Result: This study was conducted among 75 patients, which was 14.79% of the total admitted cases during study period. Maximum (62.79%) number was found in the age group of 25 to 44 years in group I and 65.62% cases in group II.  (p